Nexuses of critical minerals recovery from e-waste - Abdel Mohsen O. Mohamed (Academia Environmental Sciences and Sustainability)
Critical minerals (CMs) are essential for the development and function of renewable energy technologies, such as solar panels, wind turbines, and batteries, and for utilization in other industrial sectors, such as high-tech., automotive, information technology, aerospace, and defense. Recycling these minerals from electronic waste (e-waste) offers a sustainable solution to meet the growing industrial demand, if done technically effectively and with appropriate process inputs and rewards. This study proposes a holistic approach in addressing CMs recovery from e-waste. In doing so, seven connecting factors (nexuses) were identified and discussed. These nexuses are as follows: (i) the technical dimension that addresses the limitations of the current technologies used for e-waste recycling and recovering; (ii) the energy dimension addressing the level of consumed energy in the recycling and recovery processes; (iii) the economic dimension that addresses the economy of scale; (iv) the consumer dimension in view of consumer and manufacturer attitudes toward recycling; (v) the circularity dimension that deals with the circular design principles aiming to promote the recyclability and sustainability; (vi) the technical innovation dimension, particularly through the integration of digital technologies; and (vii) the research and development effort dimension aiming at advancing recycling technologies and recovery processes. Overcoming these limitations is crucial for maximizing resource recovery rates, reducing environmental impacts, and promoting the transition toward a more sustainable and circular economy.